Ecological Modelling of Farmland Transition: Food Web Dynamics and Multi-Objective Agricultural Optimization - Hao Rongrong; Wang Jinghan; Deng Zihui; Liu Tao (E3S Web of Conferences)
This study presents an integrated modelling framework combining ecological dynamics and agricultural decision-making to address challenges arising from forest-to-farmland conversion. A food web dynamics model simulates the energy flow and population changes across trophic levels under the influence of seasonal agricultural cycles and chemical inputs. Furthermore, a multi-objective decision support model is developed to optimize organic farming strategies that balance farmer income and ecological sustainability. Simulation results focusing on the Amazon region show that the proposed model captures ecological stabilization processes and provides actionable insights for sustainable agricultural practices.